2021
DOI: 10.1002/ajh.26212
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of D‐dimers for limb deep vein thrombosis in children: A prospective study

Abstract: The present study sought to evaluate the discriminative and predictive ability of D-dimer for pediatric limb DVT. Children aged 28 days-18 years requiring imaging to rule out limb DVT, as per the treating clinical team, were enrolled in the study. The outcome was ultrasound proven DVT. The D-dimer levels were obtained around the time of imaging. Receiver operating characteristic (ROC) curves and logistic regression models were used for data analyses. In total, 296 patients were enrolled between 2017-2020; 204 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The D-dimer test showed high sensitivity but relatively intermediate specificity at cutoff ≥500 ng/mL and AUC at 0.7. Our test performance was similar to that in Kanis et al ( 17 ) and other previous studies ( 18 , 19 ) that demonstrated high sensitivity of the D-dimer test for DVT. Additionally, a meta-analysis in adults by Stein et al reported that the sensitivity and specificity of the D-dimer test at cutoff >500 ng/mL ranged from 78% to 97% and 42% to 70%, respectively ( 9 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The D-dimer test showed high sensitivity but relatively intermediate specificity at cutoff ≥500 ng/mL and AUC at 0.7. Our test performance was similar to that in Kanis et al ( 17 ) and other previous studies ( 18 , 19 ) that demonstrated high sensitivity of the D-dimer test for DVT. Additionally, a meta-analysis in adults by Stein et al reported that the sensitivity and specificity of the D-dimer test at cutoff >500 ng/mL ranged from 78% to 97% and 42% to 70%, respectively ( 9 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, there was no significant difference in the high D-dimer level cutoff of 500 ng/mL between the tumor (55.8%) and non tumor (64.9%) groups with p -value = 0.202. The explanation is that conditions other than tumors, such as trauma, infection, inflammation, cardiac, and renal diseases, also contribute to D-dimer elevation, possibly by fibrin clot activation ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that high D-dimer values cannot be used for diagnosis of paediatric VTE, as there are no clinical studies confirming their effectiveness in the paediatric population (11,44). Moreover, in children D-dimer levels showed better discriminative and predictive ability for DVT in an exploratory sample of patients with no underlying conditions or co-morbidities at the time of diagnosis (45). However, our experience shows that in such complex situations, it could be extremely useful for guidance, considering also that it should be checked in routinely post-surgical haematological re-assessment, already frequently performed for the hormonal electrolyte imbalance risk.…”
Section: Discussionmentioning
confidence: 97%
“…Doppler ultrasound, according to several articles, is a good choice that is both readily available and dependable in both the lower and upper extremities [14,15]. D-dimer levels were found to have poor discriminative and predictive power for DVT in one study [16]. However, due of its high diagnostic sensitivity but limited specificity, a normal D-dimer is more beneficial in excluding DVT in children [17].…”
Section: Discussionmentioning
confidence: 99%